The Types and Structures of Lexical Bundles in Each Section of the Communications and Linguistics Academic Articles - Artha, Almira Fidela; Sadewa, Rahmat; Jurianto; Dewanti, Anna (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Considering its important role in applied English Linguistics, several authors have studied lexical bundles (LBs). The previous studies mainly compared the LBs between genres and among native and non-native speakers. There has yet to be any study that combines the LBs from each section of the same academic writing and the LBs of two related disciplines. This study investigates the types and structures of LBs in three rhetorical sections—Introduction, Materials and Methods, and Results and Discussion—of academic articles in the fields of Communications and Linguistics. A corpus of 3,753 journal articles (1,563 in Communications and 2,190 in Linguistics) was compiled from PLOS ONE using AntCorGen, and analyzed using AntConc Sowftware. Extended lexical bundles (four- to six-word sequences) were extracted based on frequency and dispersion thresholds. TThis study found that the variation of LBs is not only different by disciplines but also by the sections. The cooccurrence of LBs in Communication Introduction and Method is less compared to Linguistics. LBs in Communication suggest a more straightforward and clear method of conveying information. Meanwhile, Linguistics shows complexity competence and greater engagement with abstract concepts and specialized vocabulary. The trends of dominant LB structure in every section are preposition and noun-based LBs, which have higher writing quality and complexity. The study expected to highlight the importance of LBs in academic writing.